Low Anterior Resection Syndrome, Role of SNM? - Marinello, Franco (Clinics in Colon and Rectal Surgery, 2025)
Low anterior resection syndrome (LARS) includes all bowel dysfunctions after rectal cancer surgery, causing significant damage to survivors' quality of life. Among different therapeutical approaches, sacral neuromodulation (SNM) has become an interesting technique to palliate LARS symptoms. This article highlights the pathophysiology of LARS, describing the most important aspects of SNM in this scenario.
Keywords: low anterior resection syndrome; LARS; rectal cancer; sacral neuromodulation; rectal surgery